Adsorption Kinetics of Pb(II) Ions from Aqueous Solution using Modified Magnetic Nano-Composite of OPEFB - Daneshfozoun, S.; Redza, Reedzwan; Vo, Dai-Viet N.; Ramli, Nasser Mohamed; Abdullah, M. Azmuddin; Abdullah, Bawadi (Indian Journal of Science and Technology, 2017)
Background/Objectives: A batch adsorption process of Pb (II) ions from aqueous solution using modified magnetic nanocomposite from Oil Palm Empty Fruit Bunch (OPEFB). Methods: OPEFB waste was ground using grinder and hammer mill prior to magnetize using Fe2O3 to produce a nano-composite with a final size range of 0.005-0.02 mm. The adsorbent was characterized using FESEM. Batch adsorption study was performed at different temperatures (298-338K) and initial Pb concentrations (100–1000 ppm). Findings: The adsorbent morphology reveals the dense structure with pores that would increase the surface area of adsorbent. The dynamic equilibrium between fluid and solid phase is achieved approximately 60-65 min and 45 min for OPEFB and MN-EFB respectively. MN-EFB exhibits better adsorption efficiency (the best: 93.7%) as compared to raw OPEFB (the best: 78%). The pseudo-second-order kinetic fitted well with the experimental data. The activation energy of sorption obtained was 22.76 kJ mol−1 indicates that physical sorption also contributes to the adsorption process. Application/Improvements: Bio-sorbent with magnetic properties provides better removal efficiency, high reusability and suitable to be used in the industry to remove heavy metals from wastewater.